Hubungan Motivasi Belajar IPA, Pengetahuan Awal IPA, Dan Hasil Belajar IPA, Serta Identifikasi Perbedaan Hubungan Berdasar Perspektif Pesisir - Siti Aisiyah; Anik Anekawati; Nisfil Maghfiroh Meita (Wacana Didaktika, 2018)
Students of Junior High School 2 Saronggi come from coastal and non-coastal areas. The differences in the living environment will bring out a different experiences, which in turn form a diverse prior knowledge because there is a correlation between the students' experience and prior knowledge. Prior knowledge of students shows readiness to receive lessons. A student who is ready to accept learning will influence learning achievement positively. Good learning readiness results in a high of self-confidence and will focus on learning which is a characteristic of high learning motivation, therefore, it will achieve good learning achievement. The purpose of this study is to determine the relationship among learning motivation, prior knowledge, and learning achievement, and identify differences in the relationship among three variables between coastal and non-coastal students. The method in this study using experimental design One-Short Case Study, while the method of data analysis using the analysis of structural equation modeling (SEM). The results showed that there were significant correlations between the prior knowledge and learning achievement, between the prior knowledge and learning motivation, between learning motivation and learning achievement, and there was the significant difference in the relationship among learning motivation, prior knowledge and learning achievement between coastal and non-coastal students. Keywords: Science learning outcomes, learning motivation, science knowledge, SEM Abstrak Siswa SMPN 2 Saronggi berasal dari daerah pesisir dan bukan pesisir. Perbedaan lingkungan tempat tinggal akan menumbuhkan pengalaman yang berbeda, yang selanjutnya membentuk pengetahuan awal yang beragam, karena terdapat keterkaitan antara pengalaman dan pengetahuan awal siswa. Pengetahuan awal siswa menggambarkan kesiapan untuk menerima pelajaran. Siswa yang siap untuk menerima pembelajaran akan mempengaruhi hasil belajar secara positif. Kesiapan belajar yang baik memunculkan rasa percaya diri yang tinggi dan akan fokus untuk belajar yang merupakan ciri motivasi belajar tinggi, sehingga akan mencapai hasil belajar yang baik. Tujuan penelitian ini untuk mengetahui hubungan motivasi belajar IPA, pengetahuan awal IPA, dan hasil belajar IPA, serta mengidentifikasi perbedaan hubungan ketiga variabel tersebut antara siswa pesisir dan bukan pesisir. Metode pada penelitian ini menggunakan eksperimen dengan desain One-Short Case Stud, sedangkan metode analisis data menggunakan analisis structural equation modeling (SEM). Hasil penelitian menunjukkan bahwa adanya hubungan yang signifikan antara pengetahuan awal IPA dan hasil belajar IPA, antara pengetahuan awal IPA dan motivasi belajar IPA, antara motivasi belajar IPA dan hasil belajar IPA, dan terdapat perbedaan yang signifikan hubungan motivasi belajar IPA, pengetahuan awal IPA dan hasil belajar IPA antara siswa pesisir dan bukan peisisir.